Multiplicidade de Soluções para Problemas Elípticos Semilineares Envolvendo o Expoente Crítico de Sobolev - Prazeres, Disson Soares dos (2010)
In this dissertation, we study the multiplicity of solutions for the following class of semilinear elliptic problems involving the critical Sobolev exponent, ---u = - juj2---2 u + f (x; u) ; x 2 e u = 0; x 2 @ ; where N - 3, - RN is a smooth and bounded domain, - is a positive real parameter and 2- = 2N= (N - 2) is the critical Sobolev exponent. In obtaining our result, we use variational methods, such as, minimax theorems, Lusternik-Schnirelman theorems, as well as, concentration-compactness lemma.